Electrochemical corrosion resistance of aluminum alloy 6101 with cerium-based coatings in an alkaline environment - Khan, Ahsan Riaz; Zhang, Hai-Jun; Jun, Zhang; Eldin, Sayed M; Alsaiari, Norah Saleem; Katubi, Khadijah Mohammedsaleh (Frontiers in Chemistry, 2022)
Chromium-free materials as eco-friendly coatings with higher corrosion resistance are crucial in various industrial processes. Herein, we report the deposition of cerium-based conversion, a chromium-free, eco-friendly chemical conversion coating for aluminum alloy 6101, by the dip coating method. Immersion in cerium salt precursors assisted with hydrogen peroxide was performed for the deposition of cerium-based conversion coatings on aluminum alloy 6101 at different bathing temperatures. The electrochemical corrosion behavior was assessed in an alkaline solution of sodium hydroxide (pH 11), including mass loss measurements, free corrosion risk, polarization, and electrochemical impedance spectroscopy. X-ray diffraction and photoelectron spectroscopy analysis showed that the coatings were composed of Ce (III) and Ce (IV) oxides. Surface modifications and surface degradation of the coating and substrate after immersion in corrosive media were analyzed by scanning electron microscopy. Additionally, energy dispersive scanning analysis demonstrated the elemental composition before and after corrosion of the cerium salt conversion-based coating. The results demonstrated that selectively deposited cerium-based conversion coatings improved the corrosion resistance by up to 96% in a strong corrosive alkaline media.